(3GdhGVM aj GdQeis - (3YHO GdQMef Hf CMeO GdWHQjs
(3ChdgG (B:s
(3HGH ai Qei GdfTGH hai GdCUhd hGdaQhY , jfHZi def CQGO Cf jQei GdSge s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B34 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGf cTc(B/ (3GSJGfHhd (B(1/ 1933) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs